1995
DOI: 10.1139/v95-003
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of glucose by α- and β-cyclodextrins

Abstract: The concentration of glucose in aqueous solutions was monitored, using a blood glucose meter, as small weighed cyclodextrin portions were added. Equilibrium constants for the formation of inclusion complexes were calculated. A binding constant determined by this method has been verified by a technique involving competition of the guest with methyl orange indicator dye. AH' values for the reactions were estimated using calorimetry. These values along with AGO provided estimates of the standard entropies. The va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 12 publications
1
8
1
Order By: Relevance
“…While it is generally true that the formation constant of a complex between an organic compound and CD molecules would be larger in aqueous media than in organic solvents, there are cases reported in the literature in which the formation constant is larger in DMF than in water. 17,18 The formation constant measured for the complex between -D-glucose and R-CD, both dissolved in water, is reported to be 36 and 447 M -1 , 19,20 both of which are significantly smaller than the ones we obtained from our experiments. We believe this is because (1) the solubility of glucose is significantly smaller in water-ethanol mixed solvent than in water, which would the make association process more favorable, and (2) we already have decreased the entropy of the system by immobilizing the R-CD on the gold surface, making a further decrease in entropy of the reaction easier.…”
Section: Resultscontrasting
confidence: 79%
“…While it is generally true that the formation constant of a complex between an organic compound and CD molecules would be larger in aqueous media than in organic solvents, there are cases reported in the literature in which the formation constant is larger in DMF than in water. 17,18 The formation constant measured for the complex between -D-glucose and R-CD, both dissolved in water, is reported to be 36 and 447 M -1 , 19,20 both of which are significantly smaller than the ones we obtained from our experiments. We believe this is because (1) the solubility of glucose is significantly smaller in water-ethanol mixed solvent than in water, which would the make association process more favorable, and (2) we already have decreased the entropy of the system by immobilizing the R-CD on the gold surface, making a further decrease in entropy of the reaction easier.…”
Section: Resultscontrasting
confidence: 79%
“…Using the value of k s , we obtained the log K value for β-CD:glucose complex as 4.24. Hirsch et al [28] have reported the value of 2.62 for log K while the value of −0.22 for log K is reported by Hacket et al [42] from spectroscopic, fluorimetry and calorimetric measurements respectively. Considering the drawbacks of these techniques, we feel that our value of log K for β-CD:glucose complexation is much reliable.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, we came across two conflicting publications in which complexation reactions of carbohydrates with β-cyclodextrin [β-CD] as a host have been studied [28,29]. According to Hirsch et al [28], concentration of glucose can be monitored using β-CD as a complexing host.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, enzyme-less approaches using neutral carriers such as cyclodextrin and crown ethers, as ionophores for sensing biologically important molecules have received significant recent attention [13,14]. Cyclodextrins are the basket-shaped cyclic glucopyranose oligomer molecules with a hydrophobic internal cavity and hydrophilic exterior.…”
Section: Introductionmentioning
confidence: 99%